Transients analysis of a tidal currents self-balancing kinetic turbine with floating stabilizer. (15th December 2015) - Barbarelli, S.; Florio, G.; Amelio, M.; Scornaienchi, N.M.; Cutrupi, A.; Lo Zupone, G.
Highlights: New turbine recovering energy from the tidal currents able to work in the water like a kite. The turbine equilibrium represents a critical aspect of the design. Quantitative analysis of the transients which arise during the working. The floating stabilizer is a critical element which influences the trend on the transients. The sizing of the stabilizer is limited from a big visual impact. Abstract: The aim of increasing the share of renewable energy sources to the total energy production has brought a significant increase of the interest in marine energies over the last years. Within them, tidal currents resources have been gaining ground for their advantages in terms of predictability, nonexistence of extreme flows, high load factor, minimal land occupation and visual impact. The authors, working in this field since many years, have been designing a new turbine able to work in the water like a kite, with no support structures, easily connected to the coast by a rope. The constructive easiness, and the lower installation costs are the main machine characteristics, together with the ability to overturn itself when the tidal current changes direction. The turbine equilibrium and mainly the transients related to the sink and surface phases, machine overturning, represent a critical aspect of the design. In the present work, starting from a phenomenological analysis, a simulation of the transients has been carried out in Simulink® environment. The floating stabilizer is a critical component which influences the motion behavior of the machine in the vertical plane and so the trend on the transients.